2012
DOI: 10.1109/tdei.2012.6311519
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of surface discharge as indicator for hydrophobicity evaluation of silicone rubber insulators

Abstract: A Dynamic drop test (DDT) has been employed for hydrophobicity evaluation, which has proven the occurrence of different discharge phenomena in relation to the hydrophobicity variation. In this paper, based on DDT method, the characterization of surface discharges, including the discharge magnitude, pulse number, adjacent discharge magnitude and adjacent time interval, have been analyzed to evaluate the surface hydrophobicity of silicone rubber insulator. It is found that with the decrease of hydrophobicity, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…HDPE also exhibits the lowest magnitude in clean fog with enhanced surface degradations while it is the highest in salt fog with no remarkable degradation. Du et al [38] and Liu and Du [39] reported that the increase of PDs magnitude and pulse number at positive and negative cycles are well in accordance with the decrease of surface hydrophobicity. This is the case for salt fog conditions where water droplets density is higher due to the presence of salt substances which reduce the contact angle.…”
Section: Discussionmentioning
confidence: 78%
“…HDPE also exhibits the lowest magnitude in clean fog with enhanced surface degradations while it is the highest in salt fog with no remarkable degradation. Du et al [38] and Liu and Du [39] reported that the increase of PDs magnitude and pulse number at positive and negative cycles are well in accordance with the decrease of surface hydrophobicity. This is the case for salt fog conditions where water droplets density is higher due to the presence of salt substances which reduce the contact angle.…”
Section: Discussionmentioning
confidence: 78%
“…It is one of the widely used machine learning technique for both binary classification and multi-class classification problems. NBC is based on Bayes theorem to calculate the conditional probability (P H c f s ) for the given image features ( f s ) belong to a particular class of hydrophobicity (H c ) as in (10). It is simple to be constructed and suitable for high dimensionality systems…”
Section: Bayesian Classifiermentioning
confidence: 99%
“…The adjacent discharge magnitude, which is related to the discharge magnitude, represents the strength of successive discharge. Then the relationship among the number of discharge pulse, the adjacent discharge magnitude and the discharge magnitude can be obtained [30]. The changing rate of signal (d u /d t ) is calculated by the changing value (d u ) divided by the corresponding time (d t ), which was closely related to the emitting rate of PD energy.…”
Section: Experimental Specimen Facilities and Proceduresmentioning
confidence: 99%